Hydatid cyst-our institutional experience in hill area of Uttarakhand - Singh, Khem Pal; Keshri, Amit; Prakash, Sanjeev (International Journal of Medical Research and Review, 2016)
Introduction: Hydatidosis caused by Echinococcus granulosus is a neglected zoonotic disease, widely prevalent among the rural population of India. Hepatic involvement is the commonest, with other varied presentations as well. Appropriate treatment consists of surgical excision of the cyst, accompanied with chemotherapy by albendazole or PAIR procedure. Methods: This retrospective analytic study was conducted to highlight and summarise the demography, modes of presentation and surgical management and outcomes of echinococcosis at VCSGGMS & RI from years 2008-2016. Results: Most cases were adult male patients presenting with chronic manifestations of hydatidosis and/or abdominal lump (large hepatic cysts), caused by E. granulosus, who underwent surgical managament (cyst excision), along with anthelmintics and later were followed up for appropriate durations, with only minor complications. Conclusion: Timely diagnosis and intervention can prevent morbidity, mortality and economic loss among the productive sections of the society.